Manajemen Pengelolaan Pemberian Pakan dalam Menunjang Laju Pertumbuhan Udang Vanamei (Litopenaeus Vannamei) - Saripah Dewi; Karma Karma; Sulkifli Sulkifli (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The growth of vannamei shrimp is an important indicator in the success of fishery cultivation, where feeding management plays a crucial role. This study aims to determine the influence of feed management on the growth rate of vannamei shrimp and measure the contribution of these variables to growth. The research method used is a quantitative approach with the use of primary and secondary data through participatory observation at the cultivation site. Data analysis was carried out using a simple linear regression test and a determination coefficient (R²) test to answer the problem formulation empirically. The results of the regression test showed that the feed management variable had a positive effect on the Y variable (shrimp growth rate), which means that the better the feed management, the higher the growth rate of vannamei shrimp. The determination coefficient test yielded an R² value of 75.3%, indicating that feeding management made a significant contribution to shrimp growth, while 24.7% was influenced by other factors not discussed in this study. These findings confirm the importance of structured and efficient feed management in increasing shrimp farming productivity. This research is expected to be a reference for fishery business actors in designing optimal feeding strategies and encouraging further research related to other variables that also affect shrimp growth holistically.